2010
DOI: 10.1097/mcg.0b013e318198113b
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Serum N-terminal–ProBNP in Distinguishing Ascites Due to Cirrhosis From Ascites Due to Heart Failure

Abstract: Serum NT-proBNP seems to be an extremely powerful marker in distinguishing ascites due to cirrhosis from ascites due to heart failure. Serum NT-proBNP may potentially replace the more invasive testing presently in use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…This results matched with several studies [12,13]. Our study was in agreement with Sheer et al [12] where serum and ascitic fluid NT-proBNP concentrations were found to be closely related and had similar Figure 1: Serum and ascitic NT-proBNP levels in heart failure group were significantly higher than that in liver cirrhosis group (P < 0.001 for both).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This results matched with several studies [12,13]. Our study was in agreement with Sheer et al [12] where serum and ascitic fluid NT-proBNP concentrations were found to be closely related and had similar Figure 1: Serum and ascitic NT-proBNP levels in heart failure group were significantly higher than that in liver cirrhosis group (P < 0.001 for both).…”
Section: Discussionsupporting
confidence: 82%
“…This results matched with several studies [12,13]. Our study was in agreement with Sheer et al [12] where serum and ascitic fluid NT-proBNP concentrations were found to be closely related and had similar Figure 1: Serum and ascitic NT-proBNP levels in heart failure group were significantly higher than that in liver cirrhosis group (P < 0.001 for both). 36 (72) 14 (28) 22 (73.3) 8 (26.7) 18 (75) Our results were in a concordance with previous studies [12,14] that serum and ascitic fluid NT-proBNP levels with cut-off value greater than 1000 pg/ml was sensitive and specific in distinguishing patients with heart failure from those with concurrent extracellular volume overload in decompensated liver cirrhosis.…”
Section: Discussionsupporting
confidence: 82%
“…Jugular venous distension is present in the former but not in the latter. Also measurement of a blood concentration of brain natriuretic peptide or pro–brain natriuretic peptide can help distinguish ascites due to heart failure from ascites due to cirrhosis 14. The median pro–brain natriuretic peptide concentration is 6100 pg/mL in the former and only 166 pg/mL in the latter 14…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…Using a value of 1000 pg/ml, the sensitivity of serum NT-proBNP in distinguishing ascites due to cirrhosis from ascites due to heart failure was 100% [14]. Most patients with acute decompensated heart failure have high liver stiffness values which, like NT-proBNP levels tend to decrease with clinical improvement [15].…”
Section: Discussionmentioning
confidence: 99%